Morphological identification of species of the Nuneztovari Complex of Anopheles (Diptera: Culicidae) from an area affected by a Brazilian hydroelectric plant - Dos Santos, Marcia Moraes Martins; Sucupira, Izis Mônica Carvalho; Dos Santos, Thiago Vasconcelos; Dos Santos, Ana Cecília Feio; Lacerda, Raimundo Nonato Da Luz; Póvoa, Marinete Marins (Zootaxa, 2019)
The Nuneztovari Complex of Anopheles (Diptera: Culicidae) comprises four species: An. nuneztovari Gabaldon, An. goeldii Rozeboom & Gabaldon, An. dunhami Causey and An. nuneztovari species A. This study aimed to identify morphologically the species of the Nuneztovari Complex that occur in the area of the Belo Monte hydroelectric dam. The morphological identification of adult males and male genitalia (aedeagus and ventral claspette) was performed. A statistical analysis of the difference in aedeagal leaflet length was done using the Mann-Whitney test. Of the 38 male genitalia of specimens of the Nuneztovari Complex examined, 33 were identified as An. goeldii/An. nuneztovari A and five as An. nuneztovari s.s. A statistically significant difference in aedeagal leaflet length was detected between the species: the mean length was 1.23 μm for An. goeldii/An. nuneztovari A and 9.18 μm for An. nuneztovari s.s. This is the first record of An. nuneztovari s.s.in areas of environmental modification in the Brazilian Amazon. This study provides a measurement tool that can identify and differentiate species of the complex in the region, which can be applied to the other species of the complex as well to other anopheline species; thus, fostering the acquisition of information about the role of each species in malaria transmission.